IMPLEMENTASI DIGITAL MARKETING DAN CITY BRANDING “COLORFUL MEDAN” DALAM MENARIK MINAT KUNJUNGAN WISATAWAN MANCANEGARA - Zulmaini, Suciana Putri; Dirbawanto, Nana Dyki (Journal Business Administration: Entrepreneurship and Creative Industry, 2022)
Medan City in this case has great potential to become a tourist destination. This great potential is seen from its City Branding "Colorful Medan" as a diversity representation of Medan as well as the selling point of tourism promoted with digital marketing. This study aims to analyze the application of digital marketing and city branding "colorful Medan" Medan City Tourism Office has a big responsibility in developing tourism in the city of Medan. This research uses qualitative methods with descriptive approach. The locations of this study are Medan City Tourism Office. The subjects in this study are the Head of the Promotion Division, the Head of the Tourism Branding Division and a Dutch tourist. Data collection techniques consist of interview, observation and documentation. This research declares that the government of Medan has properly applied digital marketing as promotion tool for city branding "Colorful Medan". They have a website as well as various social media for communicating the tourism potential of the city of Medan to foreign tourists, although none of foreign tourist in this research is aware of the presence of either the website or social media belonging to the government of Medan.